Correlation of Mufrodat Mastery and Maharah Qira'ah Arabic Text - Fika Nadiya Ummi Salwa; Mu'at Mu'at Mu'at (Dzihni: Jurnal Pendidikan Bahasa Arab, Linguistik dan Kajian Literatur Arab, 2023)
Vocabulary which is the most important tool in Arabic language education, students can understand Arabic because they have enough vocabulary. Therefore, students' vocabulary mastery has a great impact on Arabic language education. The research questions of this study are: (1) What is the result of "vocabulary mastery" for ninth grade students at Mts "Al- Washoya" Ngoro jombang?. (2) How was the result of "Arabic text reading skills" for ninth graders in MTs" Al-Washoya" Ngoro Jombang? (3) Is there any connection between vocabulary mastery and teaching Arabic text reading skills to ninth graders in MTs "Al- Washoya" Ngoro Jombang?Â Â  In this study, a quantitative approach was carried out. The methods of data collection are: test documents and studies. The data analysis method for this study is the Verson (person) test. The results of the study that can be summarized are: (1) the results of mastering the vocabulary of the ninth grade in MTs " Al-Washoya" Ngoro Jombang. (2) As a result of teaching the skill of reading Arabic texts students in the ninth grade in MTs "Al-Washoya" Ngoro Jombang. (3) There is a relationship between mastering vocabulary and teaching the skill of reading Arabic texts to them, and this depends on the results of SPSS using analysis (Verson). From this analysis it is known that the value is 0.000 which means that the value is less than or less than 0.05, so it can be concluded that the null hypothesis HA is rejected and the alternative hypothesis HA is approved.